Evaluation of locomotor activity of pioglitazone in albino mice - L., Shruthi S.; L., Kalabharathi H.; K., Jayanthi M. (International Journal of Basic & Clinical Pharmacology, 2017)
Background: Pioglitazone (PIO), a Peroxisome Proliferator Activated Receptor γ (PPAR-γ) agonist, is an oral anti-diabetic agent belonging to the group of thiazolidinediones-TZDs used for the treatment of diabetes mellitus type 2 in monotherapy and in combination with a sulfonylurea, metformin, or insulin. Methods: All animals were allowed to acclimatize with laboratory conditions at least two weeks before starting the experiment and they were maintained under the same condition throughout the experiment. They were given food and water ad libitum. The experiments were performed as per the Committee for the Purpose of Control and Supervision on Experiments on Animals (CPCSEA) guidelines. The animals were subjected to experimentation between 0900-1600 hours in noise free atmosphere with ambient temperature 23-300ºC. Results: There was no significant reduction in the within group comparisons of the basal and final scores in locomotor activity. Conclusions: The standard and test groups failed to produce any significant reduction in locomotor activity in the intergroup comparison as well as compared to normal control.